The Influence of Halal Product Knowledge, Subjective Norms, and Consumer Attitudes on Buying Interest of Halal Snacks in UIN Syarif Hidayatullah Students Jakarta - Alifah Nur Fitria; Eny Dwiningsih; Rizki Adi Puspita Sari; Armaeni Dwi Humaerah; Mudatsir Najamuddin (Cita konsultindo, 2024)
The halal lifestyle is increasingly discussed in Indonesia, driving higher interest among Muslim consumers in halal products. This is particularly evident in the consumption of snacks, which has been rising annually and is widely consumed by students. However, snacks are often assumed to be halal even if they are not certified. This study aims to examine the impact of knowledge about halal products, subjective norms, and attitudes on purchase intention, assess the effects of halal product knowledge and subjective norms on consumer attitudes, and determine whether halal product knowledge and subjective norms influence purchase intention through consumer attitudes. Through a survey of 100 active undergraduate students at UIN Syarif Hidayatullah Jakarta and SEM-PLS analysis using SmartPLS 3.2.9, the findings are: 1) Knowledge of halal products has a significant effect on purchase intention; 2) Subjective norms have an insignificant effect on purchase intention; 3) Consumer attitudes have a significant effect on purchase intention; 4) Knowledge of halal products has an insignificant effect on attitude; 5) Subjective norms have a significant effect on attitude; 6) Knowledge of halal products has an insignificant effect on purchase intention through attitude; 7) Subjective norms have an insignificant effect on purchase intention through attitude.